Prenatal Maternal Depression Related to Allergic Rhinoconjunctivitis in the first 5 Years of Life in Children of the EDEN Mother-Child Cohort Study. Issue 3 (October 2017) - Zhou, Cailiang; Ibanez, Gladys; Miramont, Vincent; Steinecker, Magali; Baiz, Nour; Banerjee, Soutrik; Just, Jocelyne; Annesi-Maesano, Isabella; Chastang, Julie; ,
Backgroud: Evidence about the relationship between prenatal maternal depression and the development of childhood asthma and allergies in early life is scarce. We aimed to examine this relationship by using data set of EDEN mother-child cohort study. A total of 1139 children were followed-up until the age of 5 years. Methods: Prenatal maternal depression was self-reported by using the Centre for Epidemiological Studies-Depression scale (CES-D) questionnaire and was classified into binary variable (maternal depression [CES-D score of≥16] and no maternal depression [CES-D score of <16]). Asthma and allergies in the first 5 years were assessed by using the questionnaire of the International Study of Asthma and Allergies in Childhood (ISAAC). Adjusted odds ratio (aOR) was estimated for the relationship between prenatal maternal depression and early life asthma and allergies by marginal models through the method of generalized estimating equation (GEE) when adjusting for the confounders. Results: In our study population, 13.67 % of the mothers had clinical significant depression (the total scores for CES-D ≥16) during pregnancy. For children ages 5 years, the prevalence of wheezing, physician-diagnosed asthma, physician-diagnosed eczema and allergic rhinoconjunctivitis were 46.78, 20.99, 29.17, and 22.54%, respectively. Prenatal maternal depression was associated with ever allergic rhinoconjunctivitis (aOR 1.87 [95% confidence interval CI, 1.33–2.62]). No significant relationships were found between prenatal maternal depression and wheezing, physician-diagnosed asthma and physician-diagnosed eczema (aOR 1.12 [95% CI, 0.91–1.39], aOR 1.23 [95% CI, 0.81–1.85] and aOR 1.17 [95% CI, 0.86–1.61], respecitvely). Conclusion: Prenatal maternal depression was related to ever allergic rhinoconjunctivitis in the first 5 years of life in children of EDEN mother-child cohort study.